2003
DOI: 10.1046/j.1460-9568.2003.02721.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of object shape on responses of human tactile afferents under conditions characteristic of manipulation

Abstract: Most objects that we grasp, lift and further manipulate are curved, with curvatures of the same order of magnitude as those of the fingertips. Tactile information pertaining to such 'gross' geometrical features of objects are used in the automatic control of fingertip actions. We analyzed responses from 172 human tactile afferents distributed over the entire terminal phalanx when spherically shaped surfaces were applied to a standard site on the fingertip; the curvatures and force magnitudes and directions use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 84 publications
5
86
0
Order By: Relevance
“…The mechanoreceptors in the skin have been shown to be sensitive to the edges of stimuli (Phillips & Johnson, 1981). Furthermore, humans can discriminate curvatures that are pressed onto the finger pad (Goodwin, John, & Marceglia, 1991;Jenmalm, Birznieks, Goodwin, & Johansson, 2003), and they can judge the orientation of a cylinder pressed to the finger pad fairly well (Dodson, Goodwin, Browning, & Gehring, 1998). Lederman and Klatzky (1997) found that search for a target item with an edge among distractors without edges, where the items were pressed to the finger pads, was relatively efficient.…”
Section: General Methods Subjectsmentioning
confidence: 99%
“…The mechanoreceptors in the skin have been shown to be sensitive to the edges of stimuli (Phillips & Johnson, 1981). Furthermore, humans can discriminate curvatures that are pressed onto the finger pad (Goodwin, John, & Marceglia, 1991;Jenmalm, Birznieks, Goodwin, & Johansson, 2003), and they can judge the orientation of a cylinder pressed to the finger pad fairly well (Dodson, Goodwin, Browning, & Gehring, 1998). Lederman and Klatzky (1997) found that search for a target item with an edge among distractors without edges, where the items were pressed to the finger pads, was relatively efficient.…”
Section: General Methods Subjectsmentioning
confidence: 99%
“…However, the SA-IInail afferents would provide "cleaner" forcerelated signals because fine-form and textural features of the contacted object would less influence force-related signals in SAIInail afferents. Such clean signals might not only simplify computations of fingertip forces by the CNS but also help to resolve interaction effects between fingertip forces and other stimulation parameters (e.g., shape and orientation of contacted surfaces) on responses in other afferent populations (Jenmalm et al, 2003;Goodwin and Wheat, 2004).…”
Section: What Do the Sa-iinail Afferents Tell The Cns?mentioning
confidence: 99%
“…Given their abundance, in the present study we asked whether the SA-IInail afferents might contribute important information about mechanical events at volar skin areas of the fingertips that directly contact objects during natural use of the digits. Because widespread complex stresses and strains occur all over the fingertip when it deforms in response to forces applied on objects, tactile afferents not only in the skin area contacting an object, but also at the end and sides of the fingertip, can convey information about contact forces (Bisley et al, 2000;Birznieks et al, 2001;Jenmalm et al, 2003;Johansson and Birznieks, 2004). We hypothesized that also SA-IInail afferents might encode fingertip forces because of significant changes of the tension in collagenous fiber strands of the paronychium where their end organs are situated.…”
Section: Introductionmentioning
confidence: 99%
“…Neurophysiological studies have provided evidence that curvature information is processed on the basis of the response profile of the population of mechanoreceptors in the fingerpad. This response profile correlates to the contact shape and the force that is applied to the finger (Goodwin, Browning, & Wheat, 1995;Goodwin, Macefield, & Bisley, 1997;Jenmalm, Birznieks, Goodwin, & Johansson, 2003;LaMotte & Srinivasan, 1993 unsuitable to perceive the shape of weakly curved surfaces, i.e., when the curvature is below the 84% threshold of about 7 m −1 (Goodwin, John, & Marceglia, 1991;Pont, Kappers, & Koenderink, 1999).…”
Section: Exploration Modes To Perceive Curvaturementioning
confidence: 99%